The Far Right and the 2024 European Elections - Cas Mudde (Intereconomics, 2024)
In June 2024, EU citizens will vote in the European Parliament elections - two years into Russia's war in Ukraine and on European values, after the COVID-19 pandemic and the finalisation of Brexit, and with the possibility of Donald Trump winning the US presidential election later this year. In a turbulent geopolitical environment, the European Parliament elections will reshape the political landscape in Brussels, where traditional parties are being challenged and an increasing tilt towards right-wing governance is unmistakable. The current European Commission has adopted several major legislative initiatives, but a new Commission may set new priorities and take a different political direction. In the lead-up to the elections, this Forum focuses on some of the issues that will take centre stage for voters and define the next phase of European politics.
Keywords: D72; H10; 330